IOT Based 360 ÌŠ Industrial Guard System - K.Mohanraj, Dr.; G.Chinnadurai, K.; Arun, M.; Abdul Racik, K.; Sabarinathan, V. (International Journal of Engineering and Technology, 2018)
Industrial Safety is very essential and vital as it securely shields human life, predominantly in immense risk areas such as nuclear power plants, flammable oil and gases, perilous chemical, aircraft and mining industries where even a minor fault can be calamitous. Therefore, it is crucial to maintain a safe and healthy working environment with enhanced security. The proposed system ensures complete security to the industry through various applications such as detecting overheat in machine, overload detection, gas leakage detection, valve breakdown detection and employee alcohol consumption detection through various sensors and the alerts are generated by buzzer and LCD. And it can be monitored and controlled by remote user at remote place through IOT. Â Â